185k views
1 vote
Expand & simplify 3 ( c + 4 ) + 6 ( c − 5 )

1 Answer

4 votes

Answer:

9 (c - 2)

Explanation:

Simplify the following:

3 (c + 4) + 6 (c - 5)

3 (c + 4) = 3 c + 12:

3 c + 12 + 6 (c - 5)

6 (c - 5) = 6 c - 30:

12 + 3 c + 6 c - 30

Grouping like terms, 12 + 3 c - 30 + 6 c = (3 c + 6 c) + (12 - 30):

(3 c + 6 c) + (12 - 30)

3 c + 6 c = 9 c:

9 c + (12 - 30)

12 - 30 = -(30 - 12):

9 c + -(30 - 12)

| 2 | 10

| 3 | 0

- | 1 | 2

| 1 | 8:

9 c - 18

Factor 9 out of 9 c - 18:

Answer: 9 (c - 2)

User Vanducng
by
4.4k points